PERSEPSI MAHASISWA, DOSEN DAN PRAKTISI AKUNTAN INDONESIA TERHADAP EARNINGS MANAGEMENT - ISHAR BAHARUDDIN; HERU SATYANUGRAHA (Jurnal Bisnis dan Akuntansi, 2003)
Perception of accounting professions towards earning management, which is the practice of changing the amount of reported earnings was used as indicator of morality of accounting practitioners, faculty and students. This study examines the ethical acceptability of earnings management and reveals how the attitudes of the three groups differ and what variables are associated with these differences. Results indicate there are differences among the groups with students were the most lenient group and the practitioners the harshest group in judging the earnings management practice. Based on the analysis, changes in accounting education curriculum and ethics awareness programs in business for faculties were suggested.